Penerapan Dynamic Governance dalam Pengembangan Ruang Terbuka Hijau (RTH) di Kota Tangerang Selatan - Divania Yovina Putri; Mawar Mawar (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2025)
Green open space is one of the needs that cannot be ignored and is one of the elements of the city. The area of green open space in South Tangerang City has decreased because development continues to grow in each sub-district in South Tangerang City and the increase in population. Reduction of green open space caused by population density will automatically require building expansion. The purpose of this research is to find out and analyze the application of dynamic governance in the development of green open space in South Tangerang City. The method used in this research is descriptive research with a qualitative approach. This research uses theory with 3 indicators, think ahead, think again, and think across. Data collection techniques with observation, interviews, and documentation. Data analysis techniques with data reduction, data presentation, and conclusion drawing. The results showed that in the think ahead indicator, it can be said that the South Tangerang City Environmental Service has applied forward thinking because it is able to identify environmental developments, understand their implications and identify strategies needed to take advantage of new opportunities and prevent potential threats. In the thinking again indicator, it can be said that the Environment Agency of South Tangerang City has not used this thinking to achieve the desired solution in increasing the quantity of green open space. Where the percentage of green open space quantity in South Tangerang City from year to year is very slow to increase. In the thinking across indicator, it can be said that the Environment Agency of South Tangerang City has not done “learning from other cities” such as analyzing and then innovating practices that have been successfully implemented in a city. However, the Environment Agency of South Tangerang City is still trying to optimize the development of green open space in South Tangerang City.